Molecular imaging based on metabolic glycoengineering and bioorthogonal click chemistry - Yoon, Hong Yeol; Koo, Heebeom; Kim, Kwangmeyung; Kwon, Ick Chan (ELSEVIER SCI LTD, 2017)
Metabolic glycoengineering is a powerful technique that can introduce various chemical groups to cellular glycan by treatment of unnatural monosaccharide. Particularly, this technique has enabled many challenging trials for molecular imaging in combination with click chemistry, which provides fast and specific chemical conjugation reaction of imaging probes to metabolically-modified live cells. This review introduces recent progress in molecular imaging based on the combination of these two cutting-edge techniques. First, these techniques showed promising results in specific tumor cell imaging for cancer diagnosis and therapy. The related researches showed the surface of tumor cells could be labeled with bioorthogonal chemical groups by metabolic glycoengineering, which can be further conjugated with fluorescence dyes or nanoparticles with imaging probes by click chemistry, in vitro and in vivo. This method can be applied to heterogeneous tumor cells regardless of genetic properties of different tumor cells. Furthermore, the amount of targeting moieties on tumor cells can be freely controlled externally by treatment of unnatural monosaccharide. Second, this sequential use of metabolic glycoengineering and click chemistry is also useful in cell tracking to monitor the localization of the inoculated therapeutic cells including chondrocytes and stem cells. This therapeutic cell-labeling technique provided excellent viability of chondrocytes and stem cells during the whole process in vitro and in vivo. It can provide long-term and safe therapeutic cell imaging compared to traditional methods. These overall studies demonstrate the great potential of metabolic glycoengineering and click chemistry in live cell imaging. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: IN-VIVO; CELL TRACKING; TARGETED DELIVERY; CATHEPSIN-B; NANOPARTICLES; GLYCANS; SURFACES; STRATEGY